Roles & Responsibilities of Notaries in Making Wills According to Civil Law & Islamic Law - Muhammad Badruddin; Widhi Handoko (Sultan Agung Notary Law Review, 2021)
Based on the applicable legislation, the role and responsibility of a notary from the beginning to the end of the process of making a testament act is very necessary so that it has binding legal force. This writing aims to analyze the role and responsibilities of a notary for his will and protection of a notary from the perspective of the Civil Code and Islamic Law. The research method used in this thesis is a sociological juridical research method. The analytical knife used in this study uses the theory of responsibility, the theory of authority, and the theory of legal certainty. The results of the research and discussion show that the role of a Notary in making a will according to the Civil Code is in the form of: make a Supercriptie Deed relating to an explanation of a secret will and sign the deed and keep it, keep wills, keep a will in a state of war, people who sail, or those who are in places prohibited from contact with the outside world due to illness, make a deed of appointment of the executor of the will, and make a deed of appointment of the manager of the estate of the heir. The role of the Notary in making a will according to the Compilation of Islamic Law (KHI) is in the form of making a Will Deed and making a Deed of Revocation of Will. The notary's responsibility for the will, which includes moral responsibility, ethical responsibility, and moral responsibility. Protection of notaries on wills has been regulated and stated in Article 66 of the UUJN.